Organoleptic Test and Hedonic Test on Biscuits Made from Sweet Potato Leaves and Tilapia Fish - Sulastry Pakpahan; Ganda Agustina Hartati Simbolon; Tienne Artha Ulina Nadeak (Jurnal Penelitian Pendidikan IPA, 2025)
Biscuits can be a beneficial snack for who are experiencing nutritional deficiencies. Based on previous research, there has been no research on herbal biscuits, namely biscuits made from a mixture of sweet potato leaves and tilapia fish called JAMU herbal biscuits. This study aims to determine the level of consumer acceptance of JAMU herbal biscuits. The research employed a quantitative experiment, focusing on pregnant women from North Tapanuli Regency, North Sumatra, Indonesia, who served as the study's population. The sample (panelists) comprised 35 pregnant women selected through purposive sampling. We conducted the test on 35 panelists who served as organoleptic and hedonic tester examiners. The statistical analysis method we used was an analysis of variance with a difference test (post hoc test). According to the study's findings, formula A3 had the highest level of acceptance for the organoleptic test of herbal biscuits based on taste parameters, with an average of 4.69. The results of the hedonic test showed that overall panelists preferred Formula A3 JAMU herbal biscuits. According to consumers' organoleptic and hedonic tests, Formula A3 JAMU herbal biscuits had the highest level of acceptance for herbal biscuits. We hope that consumers will accept this product as a healthy option.